2019
DOI: 10.2147/ceg.s207523
|View full text |Cite
|
Sign up to set email alerts
|

<p>Reductive effect of ursodeoxycholic acid on bilirubin levels in neonates on phototherapy</p>

Abstract: Background Phototherapy is paramount in the management of high total serum bilirubin (TSB). Whether its effectiveness can be improved with ursodeoxycholic acid (UDCA) has not been evaluated among newborns of African descent. Methods A double-blind-controlled study was used to evaluate the effect of UDCA on the management of high TSB in neonates. Recruited neonates were categorized into the experimental group (given UDCA plus phototherapy) and the control group (photothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
(25 reference statements)
3
10
1
Order By: Relevance
“…Wikanthiningtyas and Mulyanti (2016) explained that bed rest during phototherapy had a significant effect on bilirubin levels in neonatal jaundice in the Neonatus High Care Unit of RSUD Dr. Moewardi with a P-val of 0.00. The results of both studies have similarities with research conducted by Ughasoro, et al (2019) explaining that phototherapy is still effective in the management of neonatal hyperbilirubinemia, but the inclusion of UDCA (urso deoxycholic acid) accentuates the reductive effect of phototherapy on total serum bilirubin in neonates, reduce the duration of treatment and inpatient care…”
Section: Photo Therapysupporting
confidence: 60%
“…Wikanthiningtyas and Mulyanti (2016) explained that bed rest during phototherapy had a significant effect on bilirubin levels in neonatal jaundice in the Neonatus High Care Unit of RSUD Dr. Moewardi with a P-val of 0.00. The results of both studies have similarities with research conducted by Ughasoro, et al (2019) explaining that phototherapy is still effective in the management of neonatal hyperbilirubinemia, but the inclusion of UDCA (urso deoxycholic acid) accentuates the reductive effect of phototherapy on total serum bilirubin in neonates, reduce the duration of treatment and inpatient care…”
Section: Photo Therapysupporting
confidence: 60%
“…Finally, as we reported in our previous experimental studies on hyperbilirubinemic Gunn rats, UDCA in clinically relevant doses substantially increased turnover of unconjugated bilirubin, with a drop of bilirubin concentrations in the vascular bed comparable to that of phototherapy 32,33 ; establishing a rationale for the use of UDCA in the treatment of severe neonatal jaundice. Indeed, this hypobilirubinemic effect of UDCA has recently been proven in several clinical studies on human neonates suffering from serious unconjugated hyperbilirubinemia, with no apparent adverse reactions attributable to administration of UDCA [34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 90%
“…The initial search yielded 376 studies, of which 17 were further assessed in the full text phase. Six RCTs were found, and of these, two were excluded: in the study by Ughasoro et al, randomization was not stratified, and children with ABO immunizations and septic newborns were included [ 23 ]; Rezaie et al included only neonates with G6PD deficiency [ 24 ]. Four RCTs were included from the initial search [ 18 , 20 – 22 ], and two additional RCTs were found from the references of included articles and included in the systematic review and meta-analysis [ 17 , 19 ] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…UDCA is generally well tolerated [ 27 ]. UDCA was reported to be effective in reducing the duration of phototherapy in healthy term neonates [ 17 – 21 ], in sick neonates [ 23 ] and among neonates with G6PD deficiency [ 24 ]. One previous study found no additional value of combining UDCA with standard phototherapy [ 22 ].…”
Section: Introductionmentioning
confidence: 99%